Hypoxia-induced Wnt/β-catenin signaling activation in subchondral bone osteoblasts leads to an osteoarthritis-like phenotype of chondrocytes in articular cartilage - Li, Fang; Tan, Qizhao; Li, Feng; Zhang, Ke; Liu, Zhongjun; Tian, Yun; Zhu, Tengjiao (Frontiers in Molecular Biosciences, 2023)
Background: Osteoarthritis (OA) is a whole-joint disease and characterized by alterations in the articular cartilage, subchondral bone, ligaments and synovial membrane. The crosstalk between cartilage and subchondral bone plays a crucial role in the pathogenesis and progression of OA. Hypoxia has been reported to play an important role in cartilage degradation and subchondral bone remodeling in OA. In this study, we aimed to identify the involvement of hypoxia in modifying the osteoblasts phenotypes and determine whether these alterations could influence the metabolic of chondrocytes. Methods: Firstly, the levels of Hif-1α in subchondral bone of different compartments in patients with OA was assessed using Immunohistochemistry (IHC). In vitro, human primary osteoblasts were cultured under hypoxic and normoxic condition, and the hypoxic or normoxic conditioned medias (HCM) (NCM) were used to culture human primary chondrocytes, respectively. Then, phenotypic changes of osteoblasts were assessed using reverse transcription-polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assays (ELISA). Further, the expressions of type II collagen (COL2A1), aggrecan (ACAN), SRY-related high mobility group-box gene9 (SOX9), matrix metalloproteinase 13 (MMP13), and matrix metalloproteinase 3 (MMP3) in chondrocytes were measured using RT-PCR. Finally, the serum levels of Wnt-related proteins were determined using ELISA. Results: The Hif-1α was significantly increased in severely sclerotic subchondral bone than less damaged subchondral bone. β-catenin and SOST were identified as upregulated and downregulated in hypoxic osteoblasts, respectively. The hypoxia induced results were confirmed by ELISA. Stimulating human primary chondrocytes with HCM significantly induced MMP13 and MMP3 and inhibited COL2A1, ACAN, and SOX9 mRNA expression. Moreover, the serum levels of DKK-1 were significantly increased in human OA. Conclusions: Together, these findings revealed that hypoxia in subchondral bone is a key factor in the crosstalk between chondrocytes and osteoblasts, and facilitate the shift of chondrocytes towards an OA-like phenotype probably by activating the Wnt/β-catenin signaling pathway in osteoblasts.